(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
In managing the number of sucking ( Aleyrodidae ) pests of citrus crops grown in our Republic today, the species composition of representatives of the Aphediidae family and their biological effectiveness against spider mites have been widely studied. It was carried out in areas infested with aphids in citrus crops and predatory and parasitic entomophagous species of aphids were identified. According to him, it was observed that these are (Neuroptera, Aphelinidae, Syrphidae, Coccinellidae, Anthocoridae, Nabidae, Miridae) families. Encarsia (Encarsia partinopea Masi ) species was used to control the amount of greenhouse whitefly (Trialeurodes vaporariorum) in greenhouse conditions , and 86.2% biological efficiency was maintained on the 28th day after applying encarsia in a ratio of 1:10 to citrus (lemon) crops in greenhouse conditions